NtWRKY-R1, a Novel Transcription Factor, Integrates IAA and JA Signal Pathway under Topping Damage Stress in Nicotiana tabacum - Jin, Weihuan; Zhou, Qi; Wei, Yuanfang; Yang, Jinmiao; Hao, Fengsheng; Cheng, Zhipeng; Guo, Hongxiang; Liu, Weiqun (Frontiers in Plant Science, 2018)
The enhancement of nicotine synthesis ability in tobacco roots can be induced by the over-ground damage, which involves the JA and auxin signal transduction. It is still unclear how these hormone signals were integrated to target nicotine synthesis. Here, we isolated NtWRKY-R1 transcription factor, which belonged to group IIe of WRKY family and had strong negative correlation with PMT expression. NtWRKY-R1 has high expression tissue specificity in tobacco roots, and there were two transcriptional activity domains in the N- and C-terminal of the NtWRKY-R1. There were the cis-elements recognized by JA and auxin signals in NtWRKY-R1 promoter. The experiment of deleting NtWRKY-R1 promoter showed that JA and auxin signals were subdued by NtWRKY-R1, which was more sensitive to auxin than JA. Yeast two-hybrid experiment showed that NtWRKY-R1 interacted with the actin-binding protein. These data showed that the intensity of JA and auxin signals can be translated into the expression of NtWRKY-R1, which regulates the balance of actin polymerization and depolymerization through binding ADF, and then regulates the expression of genes related to nicotine synthesis. These results will be helpful for understanding the functional characterization of the WRKY-IIe in crosstalk of JA and auxin under stresses.